Exploring the ESOL-PSIT relation: Interpellation, resistance and resilience. (July 2019) - Tipton, Rebecca
Abstract: This article explores the relationship between English for Speakers of Other Languages (ESOL) and Public Service Interpreting and Translation (PSIT) and the problematic juxtaposition of the two in Government discourse. I analyse the discursive construction of the ESOL/PSIT subject at different levels and problematise language support provisions as acts of interpellation, drawing on quantitative and qualitative data collected in conjunction with associates at Multilingual Manchester that shed light on lived experience of provisions. I conclude that any city-region language strategy needs to address three interrelated issues: the problem of universalising approaches to subject formation, the supply and organisation of provisions; the politicisation of 'resilience'. Highlights: The formation of the ESOL/PSIT subject varies in state and city-level discourse. Adult ESOL learners face multiple barriers to higher levels of learning. Adult immigrants resist language support provisions for complex reasons. Negative perceptions of PSIT service quality impact on interpreter requests. The conceptualisation of resilient communities neglects language proficiency.